(untitled) (The Journal of Ad-din Women’s Medical College, 2023)
Incidence of oral & laryngeal cancer in Bangladesh is increasing day by day. Neck dissection is the most commonly performed operation in any tertiary level hospital that has Head and Neck surgery and Oncology setup. Metastatic dissemination to lymph nodes of neck occurs frequently in head neck cancers which down grade the patient’s curability, shorten 5 years survival and responsible for recurrent disease. To assess complications following different types of neck dissection this cross sectional study was conducted among patients who underwent di"erent types of neck dissection due to cervical nodal metastasis and attended follow up. Common Immediate complications were hemorrhage 02 (3.33%), facial oedema 02(3.33%) and thoracic duct injury 02(3.33%). Intermediate complications were seroma (6.67%), wound infection 04 (6.67%) and chylous fistula02 (3.33%). Late Complications were hypertrophic scar 02 (3.33%) and shoulder syndrome 04(6.67%). There were no perioperative deaths. Incidence of complication can be reduced by skilled surgery, proper indications, proper identi!cation of anatomical planes along with early recognition and treatment. The Journal of Ad-din Women’s Medical College; Vol. 10 (2), July 2022; p 56-60